Strengthening Language and Eco-Cultural Literacy of the Young Generation to Support International Tourism in Karimunjawa - Kuncoro Bayu Prasetyo; Henrikus Joko Yulianto; Soeharso Soeharso (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
This article describes community empowerment for the younger generation in the Karimunjawa Islands to solve problems in local tourism development, namely low foreign language communication skills as a support for international tourism, fading knowledge and interest in local cultural arts, and the threat of tourism impacts on the ecological environment. As a problem-solving step, empowerment was carried out on youth Karang Taruna Kompak Setigi Kemajuan Karimunjawa Village to be involved and actively participate in tourism economic activities, while increasing awareness of preserving the environment and local cultural heritage.  With the Participation Rural Appraisal (PRA) method, the implementation of pre-field, field and post-field stages has succeeded in finding a pilot model in fostering motivation, skills and courage in communicating English to teenagers, while recognizing various local wisdom of traditional games that have potential as tourist attractions for foreign tourists and arousing the awareness of the younger generation to love the surrounding environment more. This is an important support for efforts to improve the welfare of the local Karimunajwa community through the international tourism economy, while preparing the younger generation of Karimunjawa as agents of guardians and preservation of Karimunjawa's culture and natural environment